Identification of Types and Levels of Physical Activity Among Students Aged 18-24 Years - Fahma Rizqi Tsa; Dona Sandy Yudasmara (Journal of Physical and Outdoor Education, 2025)
This research has been declared ethical worthy No.11.11.2/UN32.14.2.8/LT/2024. The purpose of this study is to identify physical activity and see activities that involve physical activity in leisure time in students aged 18-24 years who are currently active in lectures. The research method used descriptive quantitative with survey design through questionnaire. The instrument used in this study was a short form IPAQ physical activity questionnaire consisting of 7 main questions and 1 additional question to see the physical activities carried out in leisure time. The selection of subjects was based on the consent form distributed through several criteria, namely active students aged 18-24 years, in good health for the last 7 days, and if they have a disability, they are able to do heavy physical activity. The data analysis technique used excel with a combination of formulas from IPAQ-SF to process questionnaires and excel formulas to process data. The results showed that 47% of respondents had a high level of physical activity with an average METs score of 2903.12. Sitting activities performed during weekdays averaged 677 minutes per week or 2 hours 20 minutes per day. Leisure time activities are mostly done for sports according to the branch they like.